2022
DOI: 10.3390/molecules27154959
|View full text |Cite
|
Sign up to set email alerts
|

Application of Cleavable Linkers to Improve Therapeutic Index of Radioligand Therapies

Abstract: Radioligand therapy (RLT) is an emergent drug class for cancer treatment. The dose administered to cancer patients is constrained by the radiation exposure to normal tissues to maintain an appropriate therapeutic index. When a radiopharmaceutical or its radiometabolite is retained in the kidneys, radiation dose deposition in the kidneys can become a dose-limiting factor. A good exemplar is [177Lu]Lu-DOTATATE, where patients receive a co-infusion of basic amino acids for nephroprotection. Besides peptides, ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 67 publications
0
6
0
Order By: Relevance
“…The linker is intended to be cleaved by enzymes of the renal brush border membrane, and ideally, the formed small radiolabeled fragment is rapidly eliminated into the urine. 25,26 Pioneering work in the field of cleavable linkers for brush border membrane enzymes was performed by Yasushi Arano and colleagues based on their finding that a 3′-[ 131 I]iodohippuryl N ε -maleoyl-lysine ([ 131 I]HML)-labeled antibody fragment (Fab) liberates [ 131 I]iodohippuric acid as the major radiometabolite into the urine leading to markedly reduced activity levels in the kidneys compared to directly labeled 125 I-Fab (via tyrosine residues). 27 Based on the analysis of the subcellular distribution of activity in the kidney, the authors concluded that [ 131 I]iodohippuric acid was most likely released already at the brush border membrane and not during lysosomal degradation.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The linker is intended to be cleaved by enzymes of the renal brush border membrane, and ideally, the formed small radiolabeled fragment is rapidly eliminated into the urine. 25,26 Pioneering work in the field of cleavable linkers for brush border membrane enzymes was performed by Yasushi Arano and colleagues based on their finding that a 3′-[ 131 I]iodohippuryl N ε -maleoyl-lysine ([ 131 I]HML)-labeled antibody fragment (Fab) liberates [ 131 I]iodohippuric acid as the major radiometabolite into the urine leading to markedly reduced activity levels in the kidneys compared to directly labeled 125 I-Fab (via tyrosine residues). 27 Based on the analysis of the subcellular distribution of activity in the kidney, the authors concluded that [ 131 I]iodohippuric acid was most likely released already at the brush border membrane and not during lysosomal degradation.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Although this approach works well for somatostatin analogues and reduces the radiation dose to the kidneys between 35% and 59%, it is accompanied by side-effects such as emesis or hyperkalemia, and it is not necessarily effective for other radiopharmaceuticals. , A more general strategy for lowering the radiation exposure of the kidneys is the structural modification of the radiopharmaceutical with a cleavable linker separating the vector molecule and the radiolabel, i.e., the radiometal–chelate complex. The linker is intended to be cleaved by enzymes of the renal brush border membrane, and ideally, the formed small radiolabeled fragment is rapidly eliminated into the urine. , …”
Section: Introductionmentioning
confidence: 99%
“…This so-called concept of radioligand therapy (RLT) aims to deliver ionizing radiation to tumor cells while sparing healthy tissue. The underlying principle is the chemical linkage of the particle emitter to an antigen recognition molecule (e.g., peptides, peptidomimetics, antigens, or small molecule inhibitors) [ 17 ]. After binding to the PSMA receptor, [ 177 Lu]Lu-PSMA-617 is internalized into the PSMA positive cells, resulting in a long retention within these cells ( Figure 2 ); the high energy electrons emitted during the decay can selectively induce tissue and DNA damage, leading to cell death [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…β − emitters are most commonly used for RLT, which have a low linear energy transfer (LET). The LET is the average energy of the particle emitter that is deposited per track unit on its way [ 17 ]. The low deposited energy of β − emitters is only able to yield single-strand breaks of the DNA but can perform this over a longer range (depending on the energy of the emitted electron), which makes them especially suitable for larger tumors.…”
Section: Introductionmentioning
confidence: 99%
“…The co-infusion of amino acids and the administration of plasma expanders during therapy are efficient in reducing renal reabsorption but are also associated with adverse effects such as nausea and vomiting or with severe allergic reactions [22]. Other strategies aiming to reduce the absorbed dose to the kidneys and/or increase the kidney's radiation tolerance, such as the incorporation of a cleavable linker between the targeting ligand and the radiocomplex, are under evaluation to broaden the tolerability to PRRT and enlarge its therapeutic window [23,24].…”
Section: Introductionmentioning
confidence: 99%